Development of Egg Incubator for Detecting Embryos in Chicken Eggs Using Digital Image Processing Techniques - ลุมชะเนาว์, วิสิทธิ์ (Srinakharinwirot University Engineering Journal, 2018)
The development of the innovation of egg incubator at the present still lacks effectiveness in detecting embryos inside eggs for separating the eggs without embryos from the incubator after the incubation period of 1 to 9 days and for reducing the problem of hydrogen sulfide (H2S) from the other eggs inside the incubator in their incubation period of 18 days. The objectives of this research were: 1) to design and construct the egg incubator for detecting embryos in chicken eggs by using digital image processing techniques and 2) to find the effectiveness of the constructed incubator. The research tools were: a temperature and humidity sensor set, an egg turning control system using an electric gear motor, and a still image camera set. The research results showed that the digital image processing system displayed in white color when detecting the eggs without embryos and it displayed in black color when detecting the eggs with embryos during the incubation period of 9 to 18 days. The results from the experiment on the temperature and humidity control system revealed that the temperature value of the system could be adjusted by its automatic system with a value in the range of 34 -37.8 and the humidity value with the range 65 to 69%. And the results gained from the experiment on the effectiveness of egg hatching of 48 eggs showed that on average, 45 fertile eggs, 3 infertile eggs, 0 cracked egg, 0 rotten egg, and 93.75% of hatchability rate were found.